PENGARUH PERENCANAAN PRODUKSI TERHADAP AKTUAL PRODUKSI PADA PT UNITED TRACTORS PANDU ENGINEERING PLANT FABRIKASI - Ahmad Fauzi Nurkholis; Laisa Liza (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2023)
Production planning is an activity used to plan a production strategy for goods or services, which requires a method that can be used to plan and control the production process. The method used to plan the production process is called the Master Production Schedule (MPS). The purpose of the MPS method is to make the production process more efficient and reduce unforeseen circumstances. This study investigates the effect of production planning on actual production. The study includes MPS data from January 2023 to April 2023, for a total of 59 MPS data. Data processing was carried out using linear regression processed with IBM SPSS 25.0 software. The results showed that production planning had a significant effect on actual data by 63.90%, besides that the hypothesis test showed an influence between production planning and actual production because the significance value was smaller than 0.05. at PT. United Tractors Pandu Engineering.